2016
DOI: 10.1590/1413-812320152111.17892015
|View full text |Cite
|
Sign up to set email alerts
|

Efetividade de uma intervenção fisioterapêutica cognitivo-motora em idosos institucionalizados com comprometimento cognitivo leve e demência leve

Abstract: Efetividade de uma intervenção fisioterapêutica cognitivo-motora em idosos institucionalizados com comprometimento cognitivo leve e demência leveEffectiveness of a cognitive-motorphysiotherapeutical therapy intervention in institutionalized older adults with mild cognitive impairment and mild dementia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
1
0
7
Order By: Relevance
“…O declínio cognitivo é um dos principais motivos para institucionalização de idosos e, com frequência, contribui para o aumento da dependência na ILPI. 40 Além dos benefícios na performance funcional, o estudo de Rugbeer et al 41 comprovou que exercícios físicos em grupo, numa frequência de 3 vezes por semana, resultou em melhora na saúde mental de idosos residentes em instituições de longa permanência.…”
Section: Discussionunclassified
“…O declínio cognitivo é um dos principais motivos para institucionalização de idosos e, com frequência, contribui para o aumento da dependência na ILPI. 40 Além dos benefícios na performance funcional, o estudo de Rugbeer et al 41 comprovou que exercícios físicos em grupo, numa frequência de 3 vezes por semana, resultou em melhora na saúde mental de idosos residentes em instituições de longa permanência.…”
Section: Discussionunclassified
“…In relation to mobility, Menezes et al [26] found an improved mobility by decreasing the time to perform the TUG test of the older adults after four months of intervention with multi-component protocol; Lorca and Lepe [27] also found that the older adults perform the fastest TUG test after a year of muscle strength training, flexibility and balance. Also, studies report that dual--task training leads to better performance in the mobility of the older adults, as shorter time to perform the TUG test [14,15] and increased gait speed [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Estudos validam a importância do uso de instrumentos essenciais no rastreamento de incapacidades que são muito utilizados nas práticas de saúde, principalmente no campo da geriatria e gerontologia. CHAMPAGNE et al, 2018;MOLINA et al, 2018;ALLENDORF et al, 2016;ARAÚJO;SCATTOLIN, 2016;MENEZES et al, 2016;NUNES et al, 2016;OLIVEIRA NETA et al, 2016;ARAÚJO et al, 2015;FONTES et al, 2015;LACY, KAEMMER;CZIPRI , 2015;SOUZA et al, 2014;PEREIRA et al, 2014;RAZALI et al, 2014;SILVA et al, 2014;TUIJL et al, 2012;MENEZES et al, 2011;TAVARES et al, 2011;TORRES et al, 2010;TORRES et al 2009a;TORRES et al, 2009b;BICCA;ARGIMON, 2008).…”
Section: Introductionunclassified